The Effect of Water Ratio Variation in Soap From Cooking Oil - LATIF, AHMAD SAHLI; Ibrahim, Siti Aida (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The rate at which various waste products, such as used cooking oil (UCO), are produced is rising in line with the global population growth. The process of making soap helps spread awareness to people about the dangers of disposing of used cooking oil in rivers or drainage systems. The study focused on production on soap from cooking oil using cold method process. The ratio of oil to water to alkali was changed to make six different kinds of soap which were (20:4:3, 20:6:3, 20:8:3) for both new and used cooking oil. The research on physicochemical properties of cooking oil have been found using four different types of tests: the pH value, the moisture content test, the density test, and the Fourier transform infrared (FT-IR). There are also three types of tests have been be used to determine the physicochemical properties of the soap that has been produced: the pH value, the measurement of the foam level and stability, and the Fourier transform infrared (FT-IR). The study analyses U4 (20:4:3) soap had the best foam stability and lowest foam losses, with 98.26% and 1.74% respectively. The pH test indicated that the soap produced was alkaline with the pH of 10. The strong present of C-CH3 and CH2 group also appeared during FT-IR analysis. Sample N6 with the ratio of (20:6:3) achieved the most effective cleaning power based on the result of a study on the performance of soap made from new and used cooking oil.